2015
DOI: 10.1007/s12026-015-8737-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential cellular localization of Epstein–Barr virus and human cytomegalovirus in the colonic mucosa of patients with active or quiescent inflammatory bowel disease

Abstract: The role of human cytomegalovirus (HCMV) and Epstein-Barr virus (EBV) in the exacerbation of inflammatory bowel disease (IBD) is still uncertain. We prospectively investigated the presence of EBV and HCMV infection in both epithelial and immune cells of colonic mucosa of IBD patients, both refractory and responders to standard therapies, in comparison with patients suffering from irritable bowel syndrome who were considered as controls, by using quantitative real-time polymerase chain reaction, immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 69 publications
3
30
1
2
Order By: Relevance
“…Our investigation reveals a correlation between EBV prevalence in colonic mucosa of IBD patients and clinical disease activities. The rate of EBV positivity increased as clinical disease activities progressed, which is in accordance with Ciccocioppo's study [16]. EBV loads were further analyzed in different groups based on clinical disease activity and we found that EBV loads were higher in the severe group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our investigation reveals a correlation between EBV prevalence in colonic mucosa of IBD patients and clinical disease activities. The rate of EBV positivity increased as clinical disease activities progressed, which is in accordance with Ciccocioppo's study [16]. EBV loads were further analyzed in different groups based on clinical disease activity and we found that EBV loads were higher in the severe group.…”
Section: Discussionsupporting
confidence: 89%
“…It may be due to the difference in patients enrolled. Previous studies showed that mucosal EBV infection is associated with the severity of IBD [16]. In our study, IBD patients recruited are mainly with mild-to-moderate clinical disease activities.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study shows that the probability of CMV infection or reactivation in UC population is between 15.8% and 34.0% [8].CMV is an opportunistic virus, which has been biologically characterized by latency and activation [7].CMV infection or reactivation could signi cantly prolong the hospitalization period, increase the Corticosteroids dependence rate, operation rate and mortality [9]. The reason may be that CMV infection or reactivation could aggravate the in ammatory response and immune process, exacerbating colon damage [10]. At present, the researchers believe that CMV infection or reactivation is an independent risk factor for UC patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Y. Li et al conducted a 5-year retrospective study in IBD patients, the result of which was a conclusion that in mixed infection (CMV and C.difficile), worse outcomes are observed in patients with UC and CD [8]. Cytomegalovirus disease in patients with IBD is often a result of viral reactivation against the background of ongoing immunosuppression [9][10][11][12][13]. C. Rowan et al (2018) recommend diagnostic tests to be carried out for the detection of CMV markers in all patients with IBD occurring with febrile condition [9].…”
Section: Introductionmentioning
confidence: 99%